Legal Certainty for Auction Winners Regarding the Execution of the Object of the Dependent Rights - Dinny Octafiani; Putri Fania Marchela; Imelda Rafsodia Khoviyatu Imaniffatillah; Dadan Taufik Fathurohman; Gusti Yosi Andri (International Journal Labs, 2025)
This research discusses the legal certainty for the winner of the auction on the execution of the object of mortgage rights, especially in the context of bad credit in banking institutions. When the debtor defaults, the creditor has the right to execute the security object through auction based on Article 6 of Law No. 4 of 1996 and Article 200 HIR. Although the winner of the auction is legally valid, there are often obstacles in the physical control of the auction object due to the debtor's unwillingness to hand over the object. The research used empirical juridical method with Gustav Radbruch's legal theory approach to assess aspects of justice, certainty, and legal benefits. It was found that legal protection for auction winners includes preventive and repressive aspects, but the implementation of real execution in the field still faces various challenges, such as complex administrative processes and potential third-party claims. Therefore, regulatory improvements and inter-agency coordination are needed to ensure effective legal certainty for auction winners.